A Bronze Age Ard-Type from Hama in Syria Intended for Rope-Traction - Steensberg, Axel
I. Description of six stone blades from Hama in the Department of Classical and Oriental Antiquities at the National Museum in Copenhagen. II. Descriptions of nine stone blades and fragments of blades from Hama at the Museum in Aleppo, III. A list of 13 stone blades from Mishrifé-Qaṭna. IV. Experiments in hafting and tillage, V. Other prehistoric handimplements for tilling, VI. The adaptation of the implements. VII. Philological aspects of the word marru in describing the appearance of the implement, VIII. The function of the traction-spade and its distribution in Eurasia; ersch. 1965.